HIV/AIDS medicines and related supplies : contemporary context and procurement : technical guide (World Bank WashingtonUS, 2004)
Adapts the Bank's guidelines on the procurement of healthy goods to the HIV/AIDS context. Sets out principles and guidelines to ensure that such procurements will fit within an overall well-functioning supply management system for HIV/AIDS medicines and related supplies.
Keywords: MEDICINAL DRUGS